Relationship between Human Resource Management Practices and Employee Engagement - MB, Kavyashree; Kulenur, Sridevi; P, Nagesh; TS, Nanjundeshwaraswamy (Brazilian Journal of Operations & Production Management, 2022)
Purpose: Employee Engagement is mainstream attention for organizations in the current business scenario. The purpose of the current research focused on analysing the relationship between HRM Practices and Employee Engagement considering employees working in various IT industries, especially considering employees working in HR Department. Design/Methodology/Approach: The research was cross-sectional in nature and survey method was employed to collect the data. Exploratory Factor Analysis, Confirmatory Factor Analysis, Structural Equation Modelling were used to analyse the hypothesis. Data was collected among 345 employees employed in the HR department of various private sector organizations. Results: The model fit indices were adequate and acceptable. The model fit indices obtained were: CMIN/DF = 2.909; Goodness of Fit index (GFI) = 0.945; adjusted goodness of fit index (AGFI) = 0.909; incremental fit index (IFI) = 0.976; Tucker-Lewis index (TLI) = 0.981; comparative fit index (CFI) = 0.966; root mean square error of approximation (RMSEA) = 0.06. Findings: The results of the study disclose that HRM practices and Employee Engagement were related to each other. HRM practices in organizations empowered employees and made them more engaged to perform better in their job roles. The study results imply that HRM practices need to be considered as priority in business organizations for the long term success. Research Limitations: Non probabilistic sample method was adopted and it was possible to gather data only from 345 employees working in the HR Department of various private sector organizations. Practical Implications: Business organizations are constantly working towards adopting new strategies and programs in the workplace to empower employees and keep them engaged in their work roles and responsibilities. Therefore, organizations to focus on human resource management practices and implement them effectively to make their employees committed and engaged towards their job. In this context, the present research attempts to analyse the association between human resource practices and employee engagement. The results provide insights for business managers on the importance of having effective Human Resource practices to enhance employees level of engagement towards their work roles. Originality/ Value: Current research contributes to the existing literature on Human Resource Practices and Employee Engagement. While considering the current business scenario, it becomes very important to understand the role of human resource management practices on the engagement level of employees.